Science process skills in relation to students' achievement: a case study in SK Samarahan Estate, Serian / Nur Laili Dina Abdullah - Abdullah, Nur Laili Dina (2011)
Science Process Skills are the basis to learn Science and to practice inquiry-based learning. Additionally, Science Process Skills are interlinked with each other and if not fully mastered, it is difficult to tell apart between each of those skills. This research is aimed to identify types of Science Process Skills structure questions in Section B that students have difficulty in. Both quantitative and qualitative research methodologies were utilized in this research. The qualitative data for the research comes from a questionnaire. Meanwhile, the quantitative data were obtained from mid-year and end of the year exam paper. The findings revealed that students are generally weak and average in their SPS mastery in answering the structure questions in Section B. Students were good in interpreting data. However, they were very weak in the making inferences. The results of this research have provided some implications for the teaching of the Science in Malaysia. This action research concludes with a discussion of the findings and recommendations for future research.